Geraniaceae endémicas del Perú - Monsalve, Christhian (2006)
The Geraniaceae are represented in Peru by five genera and 59 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), mainly herbs and subshrubs. Here we recognize 18 endemic species, all in the genus Geranium. These endemic taxa are found in the Very Humid and Dry Puna, and the Mesoandean regions, between 2000 and 4800 m elevation. Two endemic Geraniaceae species have been recorded to date within Peru’s protected areas.